Decoding Patient Interactions with AI-Based Virtual Health Assistants - Zulzilah, Siti; Isa, John R.S.P.K.M. (CARAKA : Indonesia Journal of Communication, 2024)
The study examines patient interactions with virtual health assistants based on artificial intelligence in telemedicine applications, analyzing the dynamics and effectiveness of communication. The method used in this study is to use literature studies to identify trends, benefits, and challenges in integrating artificial intelligence into patient care. The findings reveal the key trends and benefits and challenges associated with integrating AI into patients' care, provide valuable insights to optimize telemedicine through AI technology, and offer practical implications for healthcare providers, policymakers, and developers. Artificial intelligence improves healthcare delivery by improving customer experience and communication between doctors and patients. However, in order for the implementation to be successful, challenges such as customer acceptance and ethical issues must be overcome. Cross-sectoral collaboration is essential for ethical compliance and better healthcare outcomes.